Leading effective engineering teams lessons for individual contributors & managers from 10 years at Google - Osmani, Addy (Ascent Audio, 2024)
In this insightful and comprehensive guide, Addy Osmani shares more than a decade of experience working on the Chrome team at Google, uncovering secrets to engineering effectiveness, efficiency, and team success. Engineers and engineering leaders looking to scale their effectiveness and drive transformative results within their teams and organizations will learn the essential principles, tips, and frameworks for building highly effective engineering teams. Osmani presents best practices and proven strategies that foster engineering excellence in organizations of all sizes. Through practical advice and real-world examples, Leading Effective Engineering Teams empowers you to create a thriving engineering culture where individuals and teams can excel. Unlock the full potential of your engineering team and achieve unparalleled success by harnessing the power of trust, commitment, and accountability. With this book, you'll discover: essential traits for engineering effectiveness and pitfalls to avoid; how to cultivate trust within your team; strategies to minimize friction, optimize career growth, and deliver maximum value; dynamics of successful engineering teams; how to implement a systems thinking approach for everyday problem-solving and decision-making; and self-advocacy techniques.
Online resource; title from title details screen (O'Reilly, viewed September 10, 2024)
Keywords: Software engineering -- Management; Computer software industry -- Management; Computer software -- Development -- Management; Project management; Logiciels; Industrie; Gestion; Gestion de projet; Audiobooks; Livres audio